Dinámica exportadora de las empresas BORN global en Colombia (2013)
This article means to analyze the main conditions of the export market for born global companies in Colombia, considering the factors in the context that primarily determine their export dynamics. For that matter we used the GEM Colombia 2011 database to analyze 297 Colombian born global firms through a descriptive analysis and through the estimation of a two-stage cluster model. Results show that technological changes, sectorial characteristics and competitive intensity are factors that determine the export dynamics of born global companies in Colombia. The paper finally concludes that entrepreneurs adapt to the international market by constantly improving their products and processes.